2019
DOI: 10.29252/ibj.23.5.8
|View full text |Cite
|
Sign up to set email alerts
|

CRB1-Related Leber Congenital Amaurosis: Reporting Novel Pathogenic Variants and a Brief Review on Mutations Spectrum

Abstract: Background: Leber congenital amaurosis (LCA) is a rare inherited retinal disease causing severe visual impairment in infancy. It has been reported that 9-15% of LCA cases have mutations in CRB1 gene. The complex of CRB1 protein with other associated proteins affects the determination of cell polarity, orientation, and morphogenesis of photoreceptors. Here, we report three novel pathogenic variants in CRB1 gene and then briefly review the types, prevalence, and correlation of reported mutations in CRB1 gene. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In addition, CRB1 mutations are responsible for 3-9% of non-syndromic arRP cases [91]. Moreover, it was observed that 9-15% of LCA cases have mutations in CRB1 [93]. Recessive CRB1 mutations may also cause CRD with MD in childhood, with electronegative ERG [94].…”
Section: Crb1mentioning
confidence: 99%
“…In addition, CRB1 mutations are responsible for 3-9% of non-syndromic arRP cases [91]. Moreover, it was observed that 9-15% of LCA cases have mutations in CRB1 [93]. Recessive CRB1 mutations may also cause CRD with MD in childhood, with electronegative ERG [94].…”
Section: Crb1mentioning
confidence: 99%
“…Additionally, CRB1 mutations account for 3% to 9% of non-syndromic arRP 50 and 9-15% of LCA cases. 51 Also, childhood CRD with macular cystic degeneration and autosomal dominant Stargardt disease phenotypes appear frequently. 52 However, clinical variability in patients with same CRB1 mutations indicates that arRP associated with CRB1 may also be modulated by other factors.…”
Section: Crb1 Genementioning
confidence: 99%
“…This difference in disease severity may be attributed to LCA being due to defective retinal progenitor cells during early ocular development, while RCD is caused by faulty photoreceptor-muller cell interaction [ 3 ]. Previous reports show that 9 to 15% of LCA cases [ 4 ] and 6.5% [ 5 ] of RCD cases result from biallelic CRB1 mutations.…”
Section: Introductionmentioning
confidence: 99%